Prevalence and associated factors of road crash involvement (RCI) among medical doctors: systematic review and meta analysis - Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Lee, Kai Wei; Ismail, Khairil Idham; Qureshi, Ahmad Munir; Ismail, Ahmad Filza; Nordin, Rusli (University of Malta, 2023)
Background: There have been vague reports on road crash involvement (RCI) affecting medical doctors with limited studies on its’ prevalence. The aim of this study is to determine the prevalence and associated factors of RCI among medical doctors. Methods: Four databases, SCOPUS, PubMed, EMBASE and Medline were systematically searched from their inception date till October 2020. Eligible studies including cross sectional studies, review articles and press reports in English underwent a systematic search to determine which articles reported on the prevalence and associated factors of RCI amongst medical doctors. Two sets of 2 independent reviewers screened the references in two steps: abstract screening, followed by full text review. The checklist Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) was used for quality assessment of the studies. Results: 599 articles were retrieved, of which 27 articles were removed after duplicate screening. The remaining 572 articles were further assessed and only 4 articles fulfilled the inclusion criteria. The RCI prevalence among medical doctors worldwide ranged from 7.9-24.6. Factors associated with increased risk of RCI include lack of sleep and fatigue related to long working hours. Other associated factors include number of years in residency, number of weekly working hours, weight gain, tendency to fall asleep while driving, hypertension, absence of breaks, inadequate rest facilities, tolerance towards shiftwork, capacity to overcome sleepiness, and quantity of night shifts worked per month. Conclusion: The prevalence of RCI among medical doctors is high. Further studies are needed to evaluate this emerging public health issue.